DEVELOPMENT OF B2B MARKETING STRATEGY AND SWOT ANALYSIS IN SUPPORTING SDGS - Muhammad Iqbal Alim El Hakim; Rahmawati, Imelda Dian (Journal of Economic and Economic Policy, 2025)
Objective: This research aims to develop an effective business-to-business (B2B) marketing strategy for the company Sartika Ratu, which is engaged in the Hajj and Umrah equipment industry. In facing the challenges of declining revenue and market share. Method: This study used a mixed method approach with a Sequential Exploratory model to gain an in-depth understanding of the internal and external factors that influence the company's marketing strategy. Data were collected through semi-structured interviews and observations, then analyzed using SWOT analysis involving IFE and EFE matrices. Results: The results showed that the company's revenue decline was related to declining B2B customer loyalty as well as challenges in attracting new customers. The SWOT analysis identified the company's key strengths in product quality and customization capabilities, while weaknesses were found in ineffective online marketing distribution. Novelty: Based on these findings, it recommended the development of a product differentiation strategy as well as the enhancement of digital distribution channels to strengthen the company's competitive position. This research also emphasizes the importance of integrating the principles of the Sustainable Development Goals (SDGs) in marketing strategies, especially in support of SDGs 8, 9, and 17. By adopting a holistic and data-driven approach, Sartika Ratu is expected to improve its competitiveness and achieve long-term sustainable growth in the Hajj and Umrah equipment industry.